Hydrogen ion supercapacitor cell construction and rational design of cell structure. (22nd August 2019) - Xie, ZhiZhong; Xu, Caiyun; Zhou, Lina; Liu, Dan; Chen, Chenyang; Tang, Haolin; Li, Junsheng; Li, Xi; Qu, Deyu
Summary: A hydrogen ion supercapacitor cell was constructed with an electrochemical double‐layer carbon material as positive electrode and an electrochemical hydrogen storage composite material as negative electrode. The electrochemical performances of both electrodes and hybrid device were investigated by varying of the mass ratio of positive and negative electrode. It was found to be that both electrodes went through the different hydrogen ion storage processes and the capacity of this hybrid supercapacitor was highly correlated with the negative to the positive electrode ratio. The highest capacity was achieved at ratio of 1:7; further increasing of this ratio may downgrade the performance of the hybrid system. With this optimized ratio, the hybrid device demonstrated good electrochemical performance. Abstract : In this hybrid supercapacitor, the charge carrier, hydrogen ion, comes from aqueous electrolyte solution. It becomes proton and then stores inside Co@NMC negative electrode during the charge process. It releases from Co@NMC electrode and adsorbs onto double layer of active carbon positive electrode during the discharge process. It rock‐chaired between positive and negative electrodes during this hydrogen ion supercapacitor operating. Novelty Statement: A new hybrid supercapacitor is developed using an electrochemical hydrogen storage cobalt/carbon composite material as negative electrode and a double‐layer porous carbon material as positive electrode. In this device, the charge carrier is hydrogen ions generated through the electrolysis of the aqueous electrolyte and, like lithium ion supercapacitor, the H ions rock‐chaired between positive and negative electrode during the operation. The structure of this new device is engineered, and the energy storage and conversion mechanisms on both electrodes during the operation are also discussed.